2020
DOI: 10.2147/clep.s226586
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patterns of Multimorbidity and Differences in Healthcare Utilization and Complexity Among Acutely Hospitalized Medical Patients (≥65 Years) – A Latent Class Approach</p>

Abstract: The majority of acutely admitted older medical patients are multimorbid, receive multiple drugs, and experience a complex treatment regime. To be able to optimize treatment and care, we need more knowledge of the association between different patterns of multimorbidity and healthcare utilization and the complexity thereof. The purpose was therefore to investigate patterns of multimorbidity in a Danish national cohort of acutely hospitalized medical patients aged 65 and older and to determine the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 59 publications
3
25
0
1
Order By: Relevance
“…In addition, depression, which is a major constituent of this pattern, is associated with increased risk of emergency hospital admissions [ 35 ]. The findings of our study are consistent with a recent Danish study, which revealed that the neuropsychiatric and mental disorders patterns had higher odds of experiencing acute hospital admissions [ 24 ]. Similarly, another Italian study showed that multimorbidity dyads including depression had a higher risk of increased annual hospitalisation days [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, depression, which is a major constituent of this pattern, is associated with increased risk of emergency hospital admissions [ 35 ]. The findings of our study are consistent with a recent Danish study, which revealed that the neuropsychiatric and mental disorders patterns had higher odds of experiencing acute hospital admissions [ 24 ]. Similarly, another Italian study showed that multimorbidity dyads including depression had a higher risk of increased annual hospitalisation days [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the varying study populations and methodologies, three patterns of multimorbidity involving cardiometabolic diseases, psychogeriatric problems and mechanical and somatoform disorders have been consistently suggested to be very prevalent in the older population [ 20 ]. The few studies that have looked at multimorbidity patterns and hospital care utilisation have some limitations, such as including only subjects aged 80 years or older [ 21 , 22 ] or already-hospitalised patients [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…Frailty and multimorbidity are commonly observed in hospitalized older patients and indicate a state of vulnerability [12][13][14]. This vulnerability likely develops well before hospitalization, but few studies have examined or characterized changes in health in the years or months leading up to an acute hospitalization.…”
Section: Introductionmentioning
confidence: 99%